The Nomenclature Policy of the Central Committee of the All-Union Communist Party (bolsheviks) in 1939–1948 - Boldovskiy, Kiryll; Pivovarov, Nikita (Pamięć i Sprawiedliwość, 2018)
The article analyzes a nomenclature policy of the VKP(b) Central Committee during the World War II and the early postwar period. As the key sources the authors study following documents: lists of nomenclature positions, reports about changes in the number of positions, information on the composition and number of executives and another documents created in the Central Committee of the VKP(b). This paper briefly explores the dynamics of the quantity of nomenclature, the internal and external factors that determined the growth and decline of nomenclature positions. The greatest increase in nomenclature positions occurred in 1939–1941, when the nomenclature of the Central Committee included almost all significant positions in the USSR at that time. During the war between the USSR and Nazi Germany, a reverse trend was indicated. It was a sharp decline in the posts of nomenclature. This decline was caused by the occupation of Soviet territories and the reduction in the party’s control over state structures. Separately, the article analyzes the personnel reform of 1946–1948, undertaken by the Secretary of the VKP(b) A.A. Kuznetsov. This article offers the reasons for the failure of this reform.